“Pasti” Pengenalan Pasar Tiban Tradisi Kliwonan Khas Buaran pada Anak Usia Dini di TK PGRI Pakumbulan - Sulistyaningsih, Wahyu (CV. Supernova Office Stationary and Printing, 2023)
The introduction of local community traditions combined with the implementation of developing entrepreneurial values in kindergarten is integrated according to themes and activities at school. Entrepreneurial values are very important to be developed in early childhood so that everything that is instilled in them can affect the development of life in the future. This research uses qualitative methods because it is carried out in natural conditions. Qualitative research focuses on how existing problems can occur rather than focusing on existing results. Using a combined cooking class and market day model.